Quality Assurance in Integrated Islamic Schools: Synergy Between National Accreditation and Internal Licensing System - Nur Azizah; Rahmat Hariyadi (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
Improving the quality of Integrated Islamic Schools (SIT) has become a pressing issue amid the dynamics of national education policy. To date, national accreditation managed by BAN-PDM functions as an external quality standard, while the Integrated Islamic School Network (JSIT) implements an internal licensing system as an additional instrument. This situation raises an academic question: what role does JSIT licensing play in complementing national accreditation as a strategy for enhancing SIT quality? This study seeks to address this question by examining the position and relevance of JSIT licensing within the broader context of educational accreditation. The research employs a literature review method with content analysis of books, national and international scholarly articles, as well as official documents issued by BAN-PDM and JSIT, particularly publications from 2019 to 2024 that are pertinent to the quality of Islamic education. The findings reveal that national accreditation emphasizes eight general standards, whereas JSIT licensing introduces eleven standards with a particular focus on the integration of Islamic values, leadership, and student development. The integration of both systems creates a significant synergy between external legitimacy and internal consistency. This study contributes to strengthening the quality of Islamic education by underscoring that the dual framework of accreditation and licensing is complementary rather than duplicative.